Profile of newborns who used Peripherally Inserted Central Catheter (PICC) in a University Hospital - Ormond, Valdelice da Silva; Azevedo, Rosemeiry Capriata de Souza; Gaiva, Maria Aparecida Munhoz; Oliveira, Daniela Fernandes de Lima (Online Brazilian Journal of Nursing, 2010)
Introduction: This study arose from the need to know as PICC has been used in neonates in order to contribute to changes in care practice, providing patient safety. Objective: To analyze the profile of newborns who used PICC in a Neonatal Intensive Care unit of a University Hospital. Method: Cross-sectional study with data obtained from medical records and analyzed using descriptive statistics. Results: Of the 484 charts reviewed, 90 (18.6%) patients used PICC. The main diagnoses were prematurity and hyaline membrane disease (26.7%). The insertion sites more used were basilic veins (37.9%) and jugular (12.9%). The main indications were infusion of parenteral nutrition (56.5) and antibiotics (12.9%). The catheters used were silicone (57.3%) and polyurethane (42.7%). The most common complication was breakage (23.2%), obstruction (17.1%), accidental withdrawal, and bacteremia (13.4%), infiltration (12.2%), phlebitis (11.0%) and malposition the catheter tip (9.8%). The catheter removal occurred mainly at the end of therapy (33.1%) and breakage of the catheter (15.3%). The average stay was 12.9 days. Conclusion: We found that the characteristics of newborns are related to national and international studies, and complications, most of them can be prevented.